Clarifying Repositioning in a Pressure Injury Context: A Scoping Review. - Iblasi, Abdulkareem S.; Yupin Aungsuroch; Joko Gunawan; Gede Juanamasta, I. (Pacific Rim International Journal of Nursing Research)
Repositioning immobilized individuals offloads pressure over the tissues and facilitates blood supply, preventing pressure injury. However, there is a gap in clarifying the practice of repositioning or standardizing the repositioning practice measurements. This scoping review aimed to clarify modes of assessing repositioning. PRISMA-ScR was used as a guideline to report the study, and The Joanna Briggs Institute Manual of Evidence Synthesis was used to conduct the scoping review. Manuscripts published between 2009 and 2021 were identified in the following databases: Cochrane Wounds Group Specialized Register, Ovid MEDLINE, EBSCO CINAHL, Clinical Key database, and Ovid MEDLINE (in-process & non-indexed citations, Jan 2009-Jan 2021), in addition to the reference sections of the potentially relevant studies. This review included English-language, interventional and non-interventional studies, department and healthcare facility reports with full-text content. This review excluded economic reviews, qualitative studies, systematic reviews, and studies that did not focus on the procedure being performed by nurses. The STROBE checklist and Downs and Black's quality assessment process were applied to check the quality of the reported article. Twenty-four studies were analyzed, four randomized, five non-randomized, and 15 had cross-sectional designs. The most common mode for measuring repositioning compliance was a chart review, used in 11 studies, followed by digital observation used in five studies; four used observation, and four used self-administered questionnaires. No measurement tool could address all issues with the accuracy and dependability of measurements. The review considers the need for a new standardized repositioning measurement instrument.